ما استشكله الحداثيون في صحيح البخاري دراسة نقدية لنماذج مختارة - قصي, الوليد (University Of Eloud جامعة الوادي, 2019)
"الملخص: الحمد لله والصلاة والسلام على رسول الله وعلى آله وصحبه ومن والاه. سأتحدث في هذا البحث عن أصحاب الفكر الحداثي؛ كيف تعاملوا مع صحيح البخاري وكيف أنهم اعتبروه مجرد أسطورة في عقول أهل الحديث, واقوم بالرد عن أفكارهم وشبهاهم حوله مدعما كلامي بعدد من الأحاديث التي استشكلوها؛ كحديث محاولة النبي الانتحار, وحديث أن النبي  جاء بالذبح, وحديث الذباب, وكيفية الرد عن تلك الأحاديث, حتى أخرج بخلاصة مفادها أن هذه الهالة التي يحاول الحداثيون إزالتها عن البخاري أقوى من شبهاتهم, وأنهم لن يستطيعوا النيل منه فلو كان في صحيحه كذب عن النبي  أو خطأ لاكتشفه أهل الاختصاص من المحدثين." "Research Summary This study deals with the view of Al-Qaradawi on dealing with the Holy Quran and understanding it, through what he wrote in the interpretation of verses of the Holy Quran, as well as through his writings in the field of science of the Koran in general. This study came in three sections, the first section introduces Dr. Qaradawi, who is a contemporary scientist that has writings in all sections of science, including interpretation and jurisprudence, advocacy and Hdith. The second section presents view of Al-Qaradawi in dealing with the Quran and understanding, these parameters, which the mark in eight concepts and the eight caveats can be occured where the interpreter and reader dealing with the Koran. Moreover, the last section presented the set of requirements that are important in dealing with the great Qur'an as an act of attribution on the side of following and the fact that the Qur'an is a constitution for governance, a method of life, and a method of advocacy. "
مذكرة ماستر تخصص علوم الحديث
Keywords: الحداثيون- صحيح البخاري - اشكالات -شبهات- ضرب السنة - مشكل الحديث- نماج مختارة- حديث الذباب- انتحار النبي- ظاهر القرآن; modern though-Saheeh al-Bukhari-the Prophet